Critical Discourse Analysis of Khadim Hussain Rizvi’s Anti-France Speeches - Sanna Asghar (University of Chitral Journal of Linguistics and Literature, 2023)
Discourse is directly connected to human emotions and feelings. The use of language and selection of words reflects the inner feeling of a person when he/she is hurt religiously. The same thing happened when France projected Prophet Muhammad (P.B.U.H) cartoons. This was shocking news for the whole Ummah because it hurt all Muslims of the world. Khadim Hussain Rizvi has shown resistance against France and recorded his protest to ban French products. The government of Pakistan assured him to fulfill this demand in the specified period. He became the voice of the whole nation. This research paper is a critical investigation of the discourses used by Rizvi in his speeches against France. Two of Rizvi’s speeches have been analyzed to show how, through the use of language, he motivates and persuades his followers to comply with his cause, and also how he manipulates his audience through the use of emotions in his speeches. The purpose was also to critically analyze the underlying ideologies and implied meanings in Rizvi’s selected speeches. Fairclough’s (1995) model of critical discourse analysis was considered liable to interpret the speeches critically in terms of discourse evaluation. The research was purely qualitative, which provided a descriptive analysis of both speeches by applying Fairclough's model. Based on the study's findings, it can be concluded that Rizvi used these approaches efficiently and widely.